PENGARUH SIFAT KIMIA TANAH TERHADAP PERTUMBUHAN TANAMAN JATI UMUR 3 TAHUN DI PETAK 14 WANAGAMA I GUNUNG KIDUL - , ALFA WIDI ASTUTI, Dr. Ir. Eny Faridah, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Environmental factors affect the growth of plants. One of the most important environmental factors influencing plant growth is soil fertility. Soil fertility is one of which can be known by the chemical properties of the soil. The purposes of this study were to determine the chemical properties of soil associated with soil the solumn depth and to examine the effect of chemical properties of soil on plant growth teak. This study was conducted in teak clone trial at compartment 14 Wanagama I Gunung Kidul. In February 2012, soil samples were taken from the different soil depths (shallow (0-10 cm), medium (0-20 cm), and deep (0-30 cm)) and measured of plant height and diameter. Analysis of N (total), P (total and available), K (total and available), Ca (total) and Mg (total) were conducted in March-May 2012. Data were analyzed using regression analysis with Microsoft Excel 2007 softwere. It was trend that the deeper ot the soil solumn the higher of available P and total Mg, and the lower of total P, available K and total Ca. While no decrease on total N and total K were observed when the soil solumn was deeper. Increasing total N ha-1, total and available P ha-1, total and available K ha-1, and total Mg ha-1 increased heigh and diameter of plant. However, increasing total Ca ha-1 did not increase the plant growth.